An Unusual Clinical Presentation of Merkel Cell Carcinoma: A Case Report - Deba P. Sarma; Dawn E. Heagley; Julianne Chalupa; Meredith Cox; James M. Shehan (Case Reports in Medicine)
Introduction. Merkel cell carcinoma is a rare, aggressive neuroendocrine cell carcinoma arising in the sun-exposed skin of elderly patients. Most of these tumors are located in the dermis. An unusual clinical presentation of such a tumor in the subcutis, if not biopsied, may be easily mistaken as a benign lesion. Case Presentation. An 83-year-old white woman presented with a several-month history of a painless 7 mm subcutaneous mass that was initially thought to be a lipoma. A conservative follow-up was planned. At the insistence of the patient, an excisional biopsy of the mass was performed revealing a subcutaneous Merkel cell carcinoma. The tumor cells stained positively for CK 20, chromogranin, and synaptophysin. No other primary or metastatic tumors found after a thorough work-up. The patient was treated with local irradiation. She remains disease free at her six-month follow-up visit. Conclusion. When a new growth is encountered in the sun-exposed skin of elderly patients, a biopsy is warranted even if the lesion clinically appears benign.